Seven Challenges in Parallel SAT Solving - Hamadi, Youssef; Wintersteiger, Christoph (Proceedings of the AAAI Conference on Artificial Intelligence, 2021)
This paper provides a broad overview of the situation in the area of Parallel Search with a specific focus on Parallel SAT Solving. A set of challenges to researchers is presented which, we believe, must be met to ensure the practical applicability of Parallel SAT Solvers in the future. All these challenges are described informally, but put into perspective with related research results, and a (subjective) grading of difficulty for each of them is provided.